A broadband and polarization-independent metasurface perfect absorber for hot-electron photoconversion. Issue 39 (4th October 2022) - Qian, Qinyu; Sun, Peiqing; Zhang, Cheng; Liu, Tingting; Chen, Haitao; Li, Fan; Cheng, Liwen; Zhao, Liang; Li, Xiaofeng; Wang, Chinhua
Abstract : We report an ultra-broadband metasurface perfect absorber from the UV to NIR region based on TiN nanostructures. Abstract : We report an ultra-broadband metasurface perfect absorber from the UV to NIR region based on TiN nanostructures. A polarization-independent experimental average absorption of 0.900 (0.921 in simulation) at the wavelength band from 300 nm to 1500 nm is realized with only an 82 nm-thick TiN layer with TiO2 and MgF2 on top, which is efficiently fabricated by utilizing double-beam UV interference lithography followed by sputter coating deposition. A TiN–TiO2 hot-electron photoelectric conversion system is also simulated. An IPCE of 4% is realized at the wavelength of 710 nm and the average IPCE is 2.86% in the wavelength range of 400 nm to 1500 nm. The demonstrated device suggests an efficient way of designing and fabricating broadband perfect absorbers, which has great application potential in efficient hot-electron optoelectronic and photocatalytic systems.